A blaVIM-2 Plasmid Disseminating in Extensively Drug-Resistant Clinical Pseudomonas aeruginosa and Serratia marcescens Isolates - Vilacoba, Elisabet (2014)
Infections caused by carbapenem-resistant Enterobacteriaceae isolates are an issue of major global concern (1). Genes coding for metallo-β-lactamases (MβLs) identified in clinical isolates are associated with mobile elements and subject to horizontal genetic transfer (HGT) events (2–6). VIM-2 is present on numerous plasmids, but only pNOR-2000 from Pseudomonas aeruginosa COL-1 from France (7, 8) and pLD209 from Pseudomonas putida LD209 from Argentina (9) have been completely sequenced. Here, we report the complete sequence and characterization of plasmid pDCPR1 harboring a blaVIM-2 gene cassette in a Tn402-type class 1 integron, which was isolated from two extensively drug-resistant strains: P. aeruginosa 802 (from a burn patient at the Hospital Municipal de Quemados, Argentina, 2005) and S. marcescens 68313 (Sanatorio Sagrado Corazón, Argentina, 2012).